PERKELAHIAN ANTAR PELAJAR DI SMAN 2 TAMBUSAI UTARA KABUPATEN ROKAN HULU - Yulestrani "; Nurhalin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This Research aim to to know (1) factor which is have conflict in SMAN 2 Tambusai Utara (2) factors causing fight between student in SMAN 2 Tambusai Utara (3) strategy or effort of[is solving of fight between student in SMAN 2 Tambusai North. this Research title is "Fight Between Student at SMAN 2 Tambusai Utara Rokan Hulu". This Research represent research using method qualitative having the character of case study, becoming its research subyek is student them which have got mixed up with fight between student and take one informan key knowing about fight in SMAN 2 Tambusai Utara, so that intake of subyek by using sampling purvosive. In conducting data collecting that is by using observation, documentation and interview. Result of this elite is known by factor cause of fight that is internal factor that is (adaptation and way of filing down) whereas factor of eksternal that is family factor, school factor (in election of chief of OSIS), and environmental factor that is (existence of difference of tribe or is ethnical, woman problem and pettishiness). In solving of fight between student that is by and konsiliasi of mediasi that is gift of educative instruction and sanction.Keyword: Conflict and Fight of Student